Single -phase heat transfer and pressure drop of water cooled at a constant wall temperature inside horizontal circular smooth and enhanced tubes with different inlet configuration in the transitional flow regime - Meyer, Josua P. (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2010.